Plasma Technology for the Enhancement of the Agriculture Sector in Nepal - Singh, Akhilesh Kumar; Baniya, Hom Bahadur; Subedi, Deepak Prasad; Joshi, Ujjwal Man (Curriculum Development Journal, 2024)
Agricultural applications of cold atmospheric pressure plasma (CAPP) technology have grown significantly during the last few years. Following harvest, using CAPP in agriculture has been the subject of numerous publications and literature reviews. However, pre-harvest plasma use is still in its infancy. Over the past five years, numerous researchers from Nepal have been using plasma technology to promote agriculture domestically and internationally. Their findings, however, are limited to scholarly publications and laboratory work. This paper explores how plasma technology can enhance Nepali agriculture, bringing it from the laboratory to the farm. A topic that has garnered a lot of attention lately is the application of plasma technology in agriculture, which is the focus of this paper. The increased focus on these studies is mostly due to the demand for less pesticide use and more intense food production. An examination of publications, concentrating on studies conducted in the past decade, identified the primary successes of plasma agro-technology as well as the primary challenges to its broad practical implementation. We examined the primary plasma source types utilized in this industry, as well as the benefits and drawbacks that dictate the application areas. Plasma technology has the potential to enhance both the quality and productivity of agriculture throughout the entire production cycle. The conditions of the plasma treatment and the efficiency of the diagnostic methods employed influence how much plasma can enhance agriculture. The possible uses of plasma technology in the field of practical agriculture will be covered in this paper. The application of plasma technology, also known as green technology, in agriculture is being brought to the attention of all stakeholders.